2020
DOI: 10.1080/14756366.2020.1801674
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activity against carbonic anhydrase IX and XII as a candidate selection criterion in the development of new anticancer agents

Abstract: Analysis of the literature data reveals that while inhibition of cancer-related carbonic anhydrase IX and XII isoforms continues to be an important enrichment factor for designing anticancer agent development libraries, exclusive reliance on the in vitro inhibition of these two recombinant isozymes in nominating candidate compounds for evaluation of their effects on cancer cells may lead not only to identifying numerous compounds devoid of the desired cellular efficacy but also to overlooking many promising ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 76 publications
(135 reference statements)
0
22
0
Order By: Relevance
“…Kinetic, crystallographic and computational data revealed that coumarins act in fact as prodrugs 40 , 41 : they undergo hydrolysis on their lactone functionality by the esterase activity of the CAs, and the corresponding 2-hydroxycinnamic acids occlude the entrance to the enzyme active site. In particular, coumarin derivatives usually behave as selective inhibitors of CAs IX and XII, which are upregulated in several hypoxic tumours 3 , 42 , and are responsible for the acidic microenvironment in tumour cells. hCA IX expression is limited in normal tissues and is considered to be a marker of aggressive and resistant tumours 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic, crystallographic and computational data revealed that coumarins act in fact as prodrugs 40 , 41 : they undergo hydrolysis on their lactone functionality by the esterase activity of the CAs, and the corresponding 2-hydroxycinnamic acids occlude the entrance to the enzyme active site. In particular, coumarin derivatives usually behave as selective inhibitors of CAs IX and XII, which are upregulated in several hypoxic tumours 3 , 42 , and are responsible for the acidic microenvironment in tumour cells. hCA IX expression is limited in normal tissues and is considered to be a marker of aggressive and resistant tumours 43 .…”
Section: Introductionmentioning
confidence: 99%
“…Sulphonamide CAIs started to be investigated as potential anti-tumour agents in the last two decades after the discovery of the two tumour-associated isoforms CA IX and XII, and their upregulation in hypoxia 3 , 4 . Nowadays, a large number of such derivatives were characterised in detail regarding their in vitro inhibitory profile against the target and off-target isoforms, but also considering pharmacokinetic and pharmacodynamics properties 26 . In fact, although many low nanomolar in vitro CAIs were reported, in cellular systems or in vivo , in animal models, not all these compounds showed the expected anti-proliferative activity 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, a large number of such derivatives were characterised in detail regarding their in vitro inhibitory profile against the target and off-target isoforms, but also considering pharmacokinetic and pharmacodynamics properties 26 . In fact, although many low nanomolar in vitro CAIs were reported, in cellular systems or in vivo , in animal models, not all these compounds showed the expected anti-proliferative activity 26 . Although such effects are reported for most classes of antitumor agents, here we evaluated three sulphonamide CAIs with very different inhibition profiles and physico-chemical properties in order to possibly address this conundrum: a positively-charged, membrane-impermeant compound (C18) with a rather selective CA IX/XII inhibition; the drug candidate in Phase Ib/II clinical trials SLC-0111 which is a CA IX/XII-selective inhibitor, and the pan-inhibitor acetazolamide.…”
Section: Discussionmentioning
confidence: 99%
“… Structures of potent and selective hCA IX/XII inhibitors from distinct classes of compounds including sulfonamides, sulfamates, coumarins, sulfocoumarins, ureidobenzenesulfonamides. Based on 133 . …”
Section: Targeting Caix With Small Molecule Inhibitorsmentioning
confidence: 99%